ATRT-16. Mechanisms of myeloid cell-induced resistance in AT/RT. (3rd June 2022) - Disch, Alina; Melcher, Viktoria; Walter, Carolin; Interlandi, Marta; Moreno, Natalia; de Faria, Flavia W; Graf, Monika; Hasselblatt, Martin; Albert, Thomas K; Kerl, Kornelius
Abstract: INTRODUCTION: Atypical teratoid/rhabdoid tumor (AT/RT) is a primary pediatric tumor entity of the central nervous system showing intra- and intertumoral heterogeneity concerning the molecular landscape and cellular composition. Myeloid cells are considered key orchestrators of the immunological tumor microenvironment (TME) of AT/RT. Tumor-infiltrating CD68 + macrophages favor chemotherapy resistance and recurrence, and are consequently related to a poor patient outcome. METHODS: Using single-cell RNA sequencing (scRNA-seq) of human and murine AT/RT samples, multiplex immunohistochemistry, depletion of myeloid cells in mouse models and advanced cell culture models for myeloid tumor cell communication, we obtained deeper mechanistic insight into these cell-cell interactions. RESULTS: Infiltrating CD68 + macrophages interact with AT/RT tumor cells generating intermediary hybrid-like cells with autonomous communication properties, increasing the cell heterogeneity of AT/RT. By depletion of myeloid cells in AT/RT mouse models followed by scRNA-seq of tumor and non-tumor samples, we demonstrated that tumor formation is hindered. Furthermore, we give mechanistic insights into how myeloid cells contribute to tumorigenesis. IN CONCLUSION: the dynamic and extensive interactions between tumor cells and myeloid cells do not only potentiate cellular heterogeneity but might also induce cellular plasticity associated with the acquisition of resistance to chemotherapy and seem to be essential for AT/RT development.